Off the Grid: Joe Pickett #16 - Box, C. J. (New York : G.P. Putnam's Sons, 2016)
When an elite special ops team recruits him to help defeat a domestic terror cell in Wyoming's Red Desert in exchange for expunging his criminal record, Nate Romanowski, assisted by Joe Pickett, discovers a sinister agenda behind the operation.
Keywords: Pickett, Joe (Fictitious character) -- Fiction; Game wardens -- Fiction; Terrorism -- Prevention -- Fiction; Pickett, Joe (Fictional character) -- Fiction; Game protection -- Fiction; Terrorism -- Prevention -- Fiction; Wyoming -- Fiction; Wyoming -- Fiction; Suspense fiction; Mystery fiction